Reliability assessment of the definition of ultrasound enthesitis in SpA: results of a large, multicentre, international, web-based study - Di Matteo, Andrea; Cipolletta, Edoardo; Destro Castaniti, Giulia Maria; Smerilli, Gianluca; Airoldi, Carla; Aydin, Sibel Zehra; Becciolini, Andrea; Bonfiglioli, Karina; Bruns, Alessandra; Carrara, Greta; Cazenave, Tomas; Ciapetti, Alessandro; et al. (Rheumatology, 2022)
OBJECTIVES: To investigate the reliability of the OMERACT US Task Force definition of US enthesitis in SpA. METHODS: In this web exercise, based on the evaluation of 101 images and 39 clips of the main entheses of the lower limbs, the elementary components included in the OMERACT definition of US enthesitis in SpA (hypoechoic areas, entheseal thickening, power Doppler signal at the enthesis, enthesophytes/calcifications, bone erosions) were assessed by 47 rheumatologists from 37 rheumatology centres in 15 countries. Inter- and intra-observer reliability of the US components of enthesitis was calculated using Light's kappa, Cohen's kappa, Prevalence And Bias Adjusted Kappa (PABAK) and their 95% CIs. RESULTS: Bone erosions and power Doppler signal at the enthesis showed the highest overall inter-reliability [Light's kappa: 0.77 (0.76-0.78), 0.72 (0.71-0.73), respectively; PABAK: 0.86 (0.86-0.87), 0.73 (0.73-0.74), respectively], followed by enthesophytes/calcifications [Light's kappa: 0.65 (0.64-0.65), PABAK: 0.67 (0.67-0.68)]. This was moderate for entheseal thickening [Light's kappa: 0.41 (0.41-0.42), PABAK: 0.41 (0.40-0.42)], and fair for hypoechoic areas [Light's kappa: 0.37 (0.36-0.38); PABAK: 0.37 (0.37-0.38)]. A similar trend was observed in the intra-reliability exercise, although this was characterized by an overall higher degree of reliability for all US elementary components compared with the inter-observer evaluation. CONCLUSIONS: The results of this multicentre, international, web-based study show a good reliability of the OMERACT US definition of bone erosions, power Doppler signal at the enthesis and enthesophytes/calcifications. The low reliability of entheseal thickening and hypoechoic areas raises questions about the opportunity to revise the definition of these two major components for the US diagnosis of enthesitis.
Keywords: reprodukovatelnost výsledků; Ultrasonography, Doppler; Ultrasonography; ultrasonografie; internet; Humans; Internet; lidé; Reproducibility of Results; Enthesopathy; ultrasonografie dopplerovská; entezopatie